Universidade e escola: dos discursos sobre a teoria e a prática no contexto do curso de letras - Cavalcanti, Marineuma de Oliveira Costa (2010)
This thesis aims to identify and analyze in the official documents that guide Brazil s Higher Education, the university role as a teaching, research and extension institution, and the Letters Course, regarding the training of Portuguese teachers. It also aims to "listen" and to examine the speeches of some professors of Pedagogical Practice for the Teaching of Portuguese Language, as well as students and former students of Letters Course, in the Universidade Estadual da Paraíba, Campus III, located in Guarabira-PB. We hope to contribute to a reflection on the theory versus practice relation in the teaching-learning process, starting with a critical view, on the initial teachers training and its impact in High School, one of the levels of professional teachers performance. As the theoretical, I make use of some fundamental concepts proposed by the French line Discourse Analysis, while the text theory focused on the relationship between the language phenomena and the social conditions of the discourse production.Furthermore, I follow considerations of some scholars of language, as well as the scholars language, who advocate a reflexive teaching, focused, mainly to the uses of the language as social interactions practices. In this way, I point that, to an effective language development proficiency of students who entrusted to us, it is urgent to promote dialogue between the university and the schools of this level, taking into account the peculiarities of the community in which they operate, and the conditions of discourses production in this context.